ANALISIS PEMASARAN CABE MERAH (Capsicum annum L.) DI KECAMATAN TALANG EMPAT KABUPATEN BENGKULU TENGAH - Elto Miko Alvaruq; Ana Nurmalia; Rika Dwi Yulihartika; Diah Azhari (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2025)
One type of horticultural product widely consumed by the community is chili. Chili is a shrub from the Solanaceae family. Chili plants consist of around 90 genera and approximately 2,000 species of herbs, shrubs, and small plants. Most of these species grow in tropical regions, although only a few can be utilized, such as potatoes (Solanum tuberosum), chili (Capsicum annum), and tobacco (Nicotiana tabacum). This research was conducted in Talang Empat Sub-district, Central Bengkulu Regency from March to April 2025. The location was purposively selected based on the consideration that farmers in the area cultivate not only rice but also red chili. The population includes all red chili farmers in Talang Empat Sub-district, totaling 30 people, all of whom were used as the sample (census). Primary and secondary data were collected through observation, interviews, and documentation. The results show that there are three marketing channels for red chili, each generating different marketing margins across institutions.